Long-Term Risks of Early Initiation of Breastfeeding to Mothers and Infants in Asia: a Systematic Review - Raisa Nurwany; Syifa Alkaf; Jeyaseelan, Ajay Varmaa (Fakultas Kedokteran Universitas Andalas, 2024)
Objective: This systematic review aims to determine the long-term risks of early initiation of breastfeeding in mothers and babies in Asia. Method: The method used in writing this literature review is systematization using keywords, namely